The Pedagogical and Professional Abilities of Pre-Service Teachers through a Project-Based Research Learning Model - Sumarmi Sumarmi; Alfyananda Kurnia Kurnia Putra; Adellia Wardatus Sholeha; Pratidina Izza Rahmasyah; Muhammad Aliman; Neni Wahyuningtyas; Wan Ibrahim Wan Ahmad (STAI Hubbulwathan Duri, 2025)
The Kurikulum Merdeka (Independent Curriculum) policy allows pre-service teachers to engage in two-semester internships, offering extended practical experience in schools. This study aimed to analyze the pedagogical and professional abilities of pre-service teachers in the digital era following the implementation of the Project-Based Research Learning model within the Teaching Assistance program. A mixed-methods approach was employed, combining quantitative and qualitative data. Research instruments included open-ended questionnaires and in-depth interviews. Data were analyzed using descriptive statistical techniques and thematic qualitative analysis. Findings revealed that pre-service teachers demonstrated strong pedagogical and professional competencies in the digital teaching environment after applying the Project-Based Research Learning model. Most participants favored group projects over individual assignments, citing benefits such as: fostering collaboration aligned with gotong royong (mutual cooperation) values, facilitating shared problem-solving, expediting project completion, and reducing individual workload. The study also identified several challenges faced by pre-service teachers during implementation, including classroom management and digital content adaptation, which are discussed in detail. The Project-Based Research Learning model effectively enhances both pedagogical and professional competencies among pre-service teachers in the digital era. Group-based projects are particularly beneficial for collaborative skill development. Future research should further explore strategies to address the challenges encountered during digital teaching practice.